‘Doing the right thing’: factors influencing GP prescribing of antidepressants and prescribed doses - Chris F. Johnson (BMC Family Practice, 2017)
Abstract Background Antidepressant prescribing continues to increase, with 5-16% of adults receiving antidepressants annually. Total prescribing growth is due in part to increased long-term use, greater selective serotonin re-uptake inhibitor (SSRI) use and the use of higher SSRI doses. Evidence does not support routine use of higher SSRI doses for depression treatment, and factors influencing the use of such doses are not well known. The aim of this study was to explore factors influencing GPs’ use of antidepressants and their doses to treat depression. Methods Semi-structured interviews with a purposive sample of 28 practising GPs; sampled by antidepressant prescribing volume, practice size and deprivation level. A topic guide drawing on past literature was used with enough flexibility to allow additional themes to emerge. Interviews were audio-recorded and transcribed verbatim. Framework analysis was employed. Constant comparison and disconfirmation were carried out across transcripts, with data collection being interspersed with analysis by three researchers. The thematic framework was then systematically applied to the data and conceptualised into an overarching explanatory model. Results Depression treatment involved ethical and professional imperatives of ‘doing the right thing’ for individuals by striving to achieve the ‘right care fit’. This involved medicalised and non-medicalised patient-centred approaches. Factors influencing antidepressant prescribing and doses varied over time from first presentation, to antidepressant initiation and longer-term treatment. When faced with distressed patients showing symptoms of moderate to severe depression GPs were confident prescribing SSRIs which they considered as safe and effective medicines, and ethically and professionally appropriate. Many GPs were unaware that higher doses lacked greater efficacy and onset of action occurred within 1-2 weeks, preferring to wait 8-12 weeks before increasing or switching. Ongoing pressures to maintain prescribing (e.g. fear of depression recurrence), few perceived continuation problems (e.g. lack of safety concerns) and lack of proactive medication review (e.g. patients only present in crisis), all combine to further drive antidepressant prescribing growth over time. Conclusions GPs strive to ‘do the right thing’ to help people. Antidepressants are only a single facet of depression treatment. However, increased awareness of drug limitations and regular proactive reviews may help optimise care.